Restauration du manuscrit Mexicain 374 de la Bibliothèque nationale de France : découverte d’une glose - Olivier Jacquot; Isabelle Bourguignon (Journal de la Société des Américanistes)
When the manuscript Mexicain 374, housed in the Bibliothèque nationale de France (BnF), was loaned to a temporary exhibition, the manuscript underwent a complete restoration. The removal of the canvas on which the document was glued made it possible to rediscover on the back of the document a gloss, probably by the author of the inventory of Lorenzo Boturini’s confiscated collections. The cleaning of the document also allowed the original colors of the manuscript to be revived, for which the scribes adopted a golden color.